Hopes, Fears, and Software Obfuscation. - BARAK, BOAZ (Communications of the ACM, 2016)
The article discusses the different aspects and applications of software obfuscation. Topics covered include the fundamental definition and potential applications of obfuscating compilers, the different features of indistinguisability obfuscators, and details relating to the structures and functions of the fully homomorphic encryption and quasi-encryption schemes.